Ultrawideband Spin‐Decoupled Coding Metasurface for Independent Dual‐Channel Wavefront Tailoring. Issue 3 (16th February 2020) - Guo, Wen‐Long; Wang, Guang‐Ming; Luo, Xin‐Yao; Hou, Hai‐Sheng; Chen, Ke; Feng, Yijun
Abstract: Achieving distinct functionalities for electromagnetic (EM) waves with opposite handedness in a broad frequency range is highly desirable and essential for modern wireless communications and radar stealth. However, available functional meta‐devices still suffer from the issues of locked functionalities or spin‐decoupled properties but with limited bandwidth. Here, a spin‐decoupled coding metasurface is presented for achieving independently spin‐controlled functionalities with high efficiency in an ultrawide frequency band. By synthesizing the Jones matrix, it is predicted that two half‐wave plates with a phase difference of 90° can form a 1‐bit coding metasurface operating for orthogonal spins independently. As proofs of concept, two meta‐devices are implemented by the metasurface in the microwave region. The first meta‐device performs as a spin‐decoupled beam deflector while the second one shows an ability to generate spin‐decoupled multi‐beams carrying desired orbital angular momentums. Both of the designed meta‐devices can operate in the whole band of 7.5–18.5 GHz (with relative bandwidth of 80%), which, to the best knowledge, is so far the broadest bandwidth that can be achieved by spin‐decoupled metasurfaces. This may trigger interest and open opportunities for advanced functional meta‐devices in practical applications, for example, multichannel metasurface antennas, or multifunctional low‐scattering devices in microwave region. Abstract : A coding methodology is reported to decouple spin‐controlled functionalities in an ultrawide frequency band. By using only two half wave plate meta‐atoms, the proposed method can enable a metasurface with independent 1‐bit phase codes for orthogonal spins, which is finally verified by two spin‐decoupled meta‐devices for either beam deflecting or generating multi‐beams carrying desired orbital angular momentums.